Deposition of NdBa2Cu3O7-δ Thin Films by Pulsed-Laser Ablation Method: Preliminary Study - Togar Saragi; A. Fuad; Darsikin Darsikin; D. Rusdiana; P. Arifin; T. Winata; M. Barmawi (Indonesian Journal of Physics, 2003)
Deposition of Nd123 thin films have been successfully produced by the pulsed-laser ablation method. The thin films were deposited at a temperature of 730oC on a MgO(100) substrate with varying oxygen flow, the distance between substrate and target, and the deposition time. The oxygen flow was 50-100 sccm, deposition time was 15 to 60 minutes with the oxygen pressure of 180 mTorr. The deposition films had a dark and shiny appearance with 1.731-11.865 Å in thickness. From the SEM and EDAX measurements, it was shown that the surface morphology has a different homogeneity and different stoichiometric composition.